Application of Technical Aspects of Animal Health in the Management of Maintenance of Beef Cattle in Seteluk District, Regency West Sumbawa - Ida Ketut Mudhita; Rosi Kusnadi; Mariyam Al Haddar; Septyana Eka Rahmawati (Journal of Tropical Animal Science and Technology, 2026)
This research seeks to explore the practical implementation of technical elements regarding beef cattle farming, covering breeding, housing, nutrition, health, and management practices in Seteluk District, West Sumbawa Regency. The investigation took place in Seteluk District, West Sumbawa at the beginning of 2025. The methodology employed for this study was the survey/observation technique involving a sample size of 100 farmers. The study's variables included respondent demographics, breeding practices, housing conditions, feeding practices, health-related factors, and management techniques. The findings indicated that all respondents were male at 100%, with farmers aged between 41 and 60 years, 53.00% having completed high school, breeding experience ranging from 1 to 20 years, and 99.00% primarily working as farmers. The implementation rates of technical aspects in beef cattle farming were as follows: 66.20% for reproduction, 40.80% for housing, 21.20% for feeding, 39.60% for health, and 38.20% for management. In conclusion, this study reveals that the overall technical aspects of cattle rearing in Seteluk Sub-district, West Sumbawa Regency are at a low percentage of 41.20%.